Intestinal Dysbiosis and Depletion of Butyrogenic Bacteria in Clostridium difficile Infection and Nosocomial Diarrhea - Antharam, Vijay C. (American Society for Microbiology, 2013)
Clostridium difficile infection (CDI) causes nearly half a million cases of diarrhea and colitis in the United States each year. Although the importance of the gut microbiota in C. difficile pathogenesis is well recognized, components of the human gut flora critical for colonization resistance are not known. Culture-independent high-density Roche 454 pyrosequencing was used to survey the distal gut microbiota for 39 individuals with CDI, 36 subjects with C. difficile-negative nosocomial diarrhea (CDN), and 40 healthy control subjects. A total of 526,071 partial 16S rRNA sequence reads of the V1 to V3 regions were aligned with 16S databases, identifying 3,531 bacterial phylotypes from 115 fecal samples. Genomic analysis revealed significant alterations of organism lineages in both the CDI and CDN groups, which were accompanied by marked decreases in microbial diversity and species richness driven primarily by a paucity of phylotypes within the Firmicutes phylum. Normally abundant gut commensal organisms, including the Ruminococcaceae and Lachnospiraceae families and butyrate-producing C2 to C4 anaerobic fermenters, were significantly depleted in the CDI and CDN groups. These data demonstrate associations between the depletion of Ruminococcaceae, Lachnospiraceae, and butyrogenic bacteria in the gut microbiota and nosocomial diarrhea, including C. difficile infection. Mechanistic studies focusing on the functional roles of these organisms in diarrheal diseases and resistance against C. difficile colonization are warranted.